2011
DOI: 10.1007/s12192-011-0255-9
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock protein 90 alpha (HSP90α) modulates signaling pathways towards tolerance of oxidative stress and enhanced survival of hepatocytes of Mugil cephalus

Abstract: Oxidative stress causes damage at the cellular level and activates a number of signaling pathways. Earlier, we have demonstrated that pollutant-related oxidative stress upregulates heat-shock protein 90 alpha (HSP90α) against stress insult in hepatocytes of Mugil cephalus living in a polluted estuary. However, the impact of pollution-induced HSP90α upregulation on stress tolerance is not clear. Here we propose that the effect of stress resistance depends on the ability of HSP90α to modulate the signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 93 publications
(105 reference statements)
2
19
0
Order By: Relevance
“…The protective effect of Hsp70 does not correlate with the intestinal morphology under heat stress, but it may be strongly correlated with the increased activity of the digestive enzymes [ 49 ]. Moreover, many signaling pathways correlated with apoptosis and protein transcription are modulated by Hsp90 to improve the tolerance to stress [ 73 ]. The study of Xie et al [ 15 ] indicated that mRNA expression of Hsp90 in the liver of broiler breeder hens increased after a long-term heat treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of Hsp70 does not correlate with the intestinal morphology under heat stress, but it may be strongly correlated with the increased activity of the digestive enzymes [ 49 ]. Moreover, many signaling pathways correlated with apoptosis and protein transcription are modulated by Hsp90 to improve the tolerance to stress [ 73 ]. The study of Xie et al [ 15 ] indicated that mRNA expression of Hsp90 in the liver of broiler breeder hens increased after a long-term heat treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp90 mRNA and protein levels were significantly increased only in the first week of exposure. A recent study on fish hepatocytes primary cultures revealed that under pollutant stress, Hsp90 overexpression blocks apoptosis by inhibiting apoptosis signal-regulating kinase 1 (ASK1) activation induced by the oxidative stress [64]. Additionally, it has been shown that Hsp90 actively supports cytoskeleton components [65], an aspect that is of great importance considering that QDs accumulation in cells might cause strain and alteration in the cytoskeleton structure [66].…”
Section: Discussionmentioning
confidence: 99%
“…These conservative changes just with different ratios coupled with the four expression patterns (especially patterns 1 and 4), could facilitate the prediction of the time-dependent differential expression of uncharacterized proteins that respond to Zn treatment. For example, proteins Hsp90α and hnRNPA1 involved in cell physiology including zinc homeostasis by previous reports were found to be significantly up- and down regulated after Zn-treatment for 24 h, respectively ( S1 File ) [ 35 , 43 46 ]. The changes in the expression of these two proteins after Zn 2+ treatment over time conformed to pattern 1 (up-regulated with rapid initial induction and subsequent repression) and pattern 4 (down-regulated with steady repression), respectively.…”
Section: Discussionmentioning
confidence: 99%